(untitled) (American Journal of Pedagogical and Educational Research, 2026)
In the context of modern education, the development of comparative thinking in students is considered one of the key factors ensuring the effectiveness and competitiveness of the learning process. This process involves training learners not only to absorb and recall information, but also to analyze, compare, contrast, and synthesize various data and phenomena. The ability to think comparatively allows students to develop a critical approach toward information, to see the similarities and differences between concepts, and ultimately, to make reasoned judgments. One of the most effective pedagogical methods for fostering comparative thinking is the targeted use of logical puzzles and problems (masalalar) in the educational environment.